How do you solve 5m - 3m + 2= 6m - 4?

3 Answers
Sep 24, 2017

m=-1.5 or -3/2

Explanation:

5m-3m+2=6m-4
2m+2=6m-4
2m-6m=-4-2
-4m=6
4m=-6
m=-6/4=-3/2 or -1.5

Sep 24, 2017

See a solution process below:

Explanation:

First, combine like terms on the left side of the equation:

5m - 3m + 2 = 6m - 4

(5 - 3)m + 2 = 6m - 4

2m + 2 = 6m - 4

Next, subtract color(red)(2m) and add color(blue)(4) to each side of the equation to isolate the m term while keeping the equation balanced:

2m - color(red)(2m) + 2 + color(blue)(4) = 6m - color(red)(2m) - 4 + color(blue)(4)

0 + 6 = (6 - color(red)(2))m - 0

6 = 4m

Now, divide each side of the equation by color(red)(4) to solve for m while keeping the equation balanced:

6/color(red)(4) = (4m)/color(red)(4)

(2 xx 3)/color(red)(2 xx 2) = (color(red)(cancel(color(black)(4)))m)/cancel(color(red)(4))

(color(red)(cancel(color(black)(2))) xx 3)/color(red)(color(black)(cancel(color(red)(2))) xx 2) = m

3/2 = m

m = 3/2

Sep 24, 2017

m=1.5

Explanation:

First do the subtraction 5m-3m:
2m+2=6m-4

Then rearrange the equation to have m's on one side and numbers on the other. Do the subtraction and addition of 6m-2m
and 4+2

6m-2m=2+4->4m=6

Divide by 6 to isolate m and simplify the fraction:
m=6/4->3/2->1.5

m=1.5